Development of a new fertilizer material from the shell of the inga feuillei for ecofriendly pens using design thinking (LACCEI, 2024)
The writing is inherent to the human being, initially goose feathers were used with ink or reeds to then move to plastic pens, however they are disposable or easily replaced in the face of some loss due to their low cost, but this attracts an increase in environmental pollution as very few plastics are properly recycled. Today, alternatives have appeared to use eco-friendly materials such as paper, cardboard, coconut shell waste and bamboo, However none of these alternatives is really eco-friendly under a circular economy where the manufacturer must consider a significant added value. Therefore, using the innovative product design methodology of Desing Thinkins, we propose a pen with an ergonomic design with a seed at the tip manufactured with a completely organic material such as fertilizer with good properties in macronutrients such as NPK. The result of this research is that the proposed material requires less energy than its current competition to be effectively used as a fertilizer with a significant result since it does not require to be burned to use as a biocarbon or ash and has high ranges in the macronutrients analysed in the laboratory, in addition to being completely organic and requiring water to initiate its degradation as compostable material.